2020
DOI: 10.1088/1361-6528/aba5b7
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of ferroelectric properties in Hf0.5Zr0.5O2 between thermal and plasma-enhanced atomic layer deposition

Abstract: Since the discovery of ferroelectricity in doped/alloyed HfO2 and ZrO2 thin film, many device engineers have been attracted to its sustainable ferroelectricity at the thickness of a few nanometer. While most of the previous studies have mainly focused on the ferroelectric properties of the thermally atomic layer deposited (THALD) Hf0.5Zr0.5O2 (HZO), the plasma-enhanced ALD (PEALD) HZO has not received much attention. In this work, a direct comparison between the two types of HZO thin films is carried out, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…It is reported that the use of H2O2 or O plasma at the initial stage of film growth to suppress oxygen vacancy accumulation at the bottom electrode [21]. In addition, the film grown with plasmaenhanced ALD (PEALD) has also been reported for the oxygen vacancy reduction, leading to higher breakdown voltage and thus better TDDB performance [22].…”
Section: ◼ Discussionmentioning
confidence: 99%
“…It is reported that the use of H2O2 or O plasma at the initial stage of film growth to suppress oxygen vacancy accumulation at the bottom electrode [21]. In addition, the film grown with plasmaenhanced ALD (PEALD) has also been reported for the oxygen vacancy reduction, leading to higher breakdown voltage and thus better TDDB performance [22].…”
Section: ◼ Discussionmentioning
confidence: 99%
“…The proposed modeling framework was used to extract ferroelectric parameters for Al-doped 6,7 , Gd-doped 8 , La-doped 9 , Si-doped 1,[10][11][12] , Sr-doped 13 , Y-doped 14,15 , Zr-doped 4,10,[16][17][18][19][20][21][22][23][24][25][26] , and undoped 4,5 HfO 2 thin films reported in the literature as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroelectric field-effect transistors (FeFETs), as emerging memory, find a niche in such applications due to their ultra-fast program/erase time, low operation voltage, and low power consumption [1][2][3] . Despite the fact that hafnium oxide 4,5 and its doped variants (Al-doped 6,7 , Gd-doped 8 , La-doped 9 , Si-doped 1,[10][11][12] , Sr-doped 13 , Y-doped 14,15 , Zr-doped 4,10,[16][17][18][19][20][21][22][23][24][25][26] ) have been extensively studied and characterized over the past few years, little has been done to aggregate those data into ferroelectric properties to provide the insight necessary to create a predictive model for ferroelectrics. Such a predictive model cannot be realized without the accurate determination of a multitude of ferroelectric parameters from various experimental hysteresis loops (Q FE -E FE ).…”
Section: Introductionmentioning
confidence: 99%
“…We extracted those ferroelectric parameters from the experiments of our group's previous research [10]. The plasma enhanced ALD was used for depositing the Hf0.5Zr0.5O2 layer in [13]. Fig.…”
Section: Simulation Methodsmentioning
confidence: 99%